KERAHIMAN SEBAGAI INTISARI INJIL DALAM TEOLOGI WALTER KASPER DAN PAUS FRANSISKUS - Arifin, Vinsensius Rosihan (P3TK, Sanata Dharma University, 2017)
This research aims to make an observation on theology of mercy. Two important theologians who take seriously mercy as the essence of the Gospel are Cardinal Walter Kasper and Pope Francis. Mercy as the essence of the Gospel is the hypothesis of this thesis. To prove that hypothesis, the writer had two foundational questions: what are similarity and difference of both thinkers. To answer those questions, the writer proposes several other questions: what is the background of their thought, what are their theological and pastoral views on the theology of mercy. This study based on a textual research with two methods, text analysis and comparative method. First, with text analysis method, the writer will read, observe, and analyze the works of Walter Kasper and Pope Francis about theology of mercy. Second, with comparative method, the writer will try to make parallelism of both thoughts to come to a synthesis about mercy as the essence of the Gospel. From that synthesis, the writer will make theological reflection and relevance for the present Church, especially in Indonesia and particularly the Archdiocese of Jakarta.